Religious commitment and spiritual well-being as predictors of happiness among middle-aged Chinese catholics - Li, Weiping (Animo Repository, 2013)
This present study is aimed to investigate the relationship between religious commitment, spiritual well-being and happiness/SWB among middle-aged Chinese Catholics. A quantitative study utilizing a cross-sectional design was employed. Three hundred (300) participants from different cities in China were invited to complete four instruments: the Satisfaction with Life Scale (SWLS), Positive and Negative Affect Schedule (PANAS), Religious Commitment Inventory-10(RCI) and Spiritual Well-Being Scale (SWBS). Data analysis was completed employing a series of multiple regressions to ascertain the correlations of the aforementioned constructs. The findings revealed that religious commitment (including intrapersonal and interpersonal domains) and spiritual well-being (including personal, communal, environmental, transcendental domains) are significant predictors for happiness/SWB. The descriptive statistical analysis indicate that the participants share a high level of life satisfaction and positive affect, but moderate level of negative affect. It was also found that the participants expressed a high level of religious commitment and spiritual well-being.